Pengembangan LKPD Mitigasi Bencana Gempa Bumi Melalui TTS dan Cerita Rumpang Pada Siswa Kelas IV SD - Amelia Dewi Sofyan; Nurul Istiq’faroh; Wardah Shabira Nurfaizah (CV. Kurnia Grup, 2026)
The purpose of this study was to develop worksheets on earthquake disaster mitigation using crossword puzzles and cloze exercises, and to test their validity and practicality among fourth-grade students at SDN Klurak Sidoarjo. The study employed a Research and Development method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The results showed that the worksheets achieved 98.61% content validity and 100% media validity, placing them in the “highly valid” category. The practicality test also revealed positive responses from teachers and students, as the worksheets were easy to use, engaging, and aided in understanding the material. These findings align with the characteristics of cloze exercises, which support reading comprehension, vocabulary development, and critical thinking, as well as crossword puzzles, which have been proven to enhance vocabulary and learning engagement. Thus, the developed worksheets are suitable for use as innovative thematic teaching materials to improve language literacy and disaster mitigation awareness among students.